Competition for the Elements of the City Environment for Irkutsk’s Public Spaces: Street Furniture, Street Design - Danilova, Tatyana (project baikal, 2015)
The article reviews the contest «Street furniture. Street design», which was held this summer by manufacturing company «PalpNord», International research laboratory of study and design of the urban environment «Urban Planning School» and the Union of Architects of Russia. The winners and their projects are also listed in the article.
Keywords: street furniture; city environment; small architectural forms